Komitmen Pemimpin dalam Mengembangkan Ruang Terbuka Hijau di Kabupaten Kudus - Intan Istiqomah; Titik Djumiarti (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2016)
Green open space (RTH) issue has been part of the municipal government of Kudus Regency policy. However, the policy had not been implemented effectively for there was only 8% of the total spaces available in the regency were used for the green open space. Participation of concerned stakeholders are necessary towards further development of the green open space (RTH). This research is a qualitative descriptive research which is aimed to know the commitment of leaders in developing Green Open Space in Kudus Regency and obstacle factors related to commitment of leaders in development of Green Open Space. This descriptive-qualitative study aimed to find out local leadership commitment in Kudus Regency to the development of the green open area (RTH). The study found that the local leaders did not have optimal commitment, as it might be evident from attitudes of leading by example, role in decision-making process, and promises to stipulate necessary local laws. The study also found some impending factors such as ineffective communiation in distributing information related to green open area, lacking competency among employees, and inadequate facilities. The study recommended improvement of some local leadership supporting indicators. Authorities in the municipal government of Kudus Regency must lead by examples, provide unused area for the green open space project, and improve competencies of the employees. Education and training programs, as well as seminars, are necessary to improve human resource development. In addition, local laws concerning the green open area must be enforced.